Intestinal microsporidiosis among children with cancer : an update. - Awang Hamat, Rukman (Universiti Putra Malaysia Press, 2012)
Microsporidiosis is a disease caused by microsporidia, which are single-celled, obligate intracellular parasites that infect a broad range of invertebrates and vertebrates including humans. The first microsporidia species identified by Nägeli in 1857 was named as Nosema bombycis [1]. This parasite was responsible for the pebrine disease that killed silkworms resulting in substantial economic losses to silk and other insect-related industries in a few European countries. However, greatest concerns on microsporidia arose from a few documented cases of microsporidiosis in humans and from a single report on persistent diarrhea, weight loss and wasting syndrome in a person with acquired immunodeficiency syndrome (AIDS) [2, 3]. Since then, microsporidia have been recognized as one of the etiological agents causing opportunistic infections associated with significant morbidity and mortality in this type of immunocompromised patients [4, 5].